Optimizing Zakat Potential Management to Achieve SDGs: Case in BAZNAS of North Sumatera, Indonesia - Umar, M. Ridwan; Syahbudi, Muhammad; Rahayu, Sri; Nasution, Venny Fraya Hartini; Ichsan, Reza Nurul (LPPM, Universitas Islam Syarifuddin Lumajang, 2025)
The Sustainable Development Goals (SDGs) are sustainable development programmes that are an advanced programme of the MDGs or Millennium Development Objectives. Zakat is a major factor in the expropriation of the property of the Muslims, with 85% of Indonesians Islamic, Islamic in North Sumatra itself is 66%, and the province's potential zakat ranks sixth out of 34 provinces. It can help the success of these SDGs. This research uses a qualitative research approach with the type of research Study and Case Documentation. This method of research with a qualitative approach is used to analyze the potential impact of achieving SDGs through Zakat in BAZNAS North Sumatra. It has been found that many previous studies have discussed the BAZNAS of North Sumatra which have not been able to scan economic growth but are able to minimize poverty. Various programmes are proposed to create SDMs that support the achievement of the SDGs. This study provides practical insights for policymakers and zakat institutions globally, emphasizing the importance of integrating zakat frameworks into national and international development agendas.